2020
DOI: 10.3390/ijms21031095
|View full text |Cite
|
Sign up to set email alerts
|

Small Vessel Disease-Related Dementia: An Invalid Neurovascular Coupling?

Abstract: The arteriosclerosis-dependent alteration of brain perfusion is one of the major determinants in small vessel disease, since small vessels have a pivotal role in the brain’s autoregulation. Nevertheless, as far as we know, endothelium distress can potentiate the flow dysregulation and lead to subcortical vascular dementia that is related to small vessel disease (SVD), also being defined as subcortical vascular dementia (sVAD), as well as microglia activation, chronic hypoxia and hypoperfusion, vessel-tone dysr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 359 publications
(436 reference statements)
4
61
0
Order By: Relevance
“…Regarding other risk factors of dementia, several cardiovascular diseases lead to a higher rate of dementia development, which may due to the correlation of vessel damage and brain degeneration proven in previous research [1,7,8,23]. Besides, DM is associated with the occurrence of cardiovascular disease and can also lead to certain types of dementia, which correlated to the finding of the current study [9].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding other risk factors of dementia, several cardiovascular diseases lead to a higher rate of dementia development, which may due to the correlation of vessel damage and brain degeneration proven in previous research [1,7,8,23]. Besides, DM is associated with the occurrence of cardiovascular disease and can also lead to certain types of dementia, which correlated to the finding of the current study [9].…”
Section: Discussionsupporting
confidence: 84%
“…The advanced age accounts for the majority of involution dementia worldwide [1], while depression may play a role in general dementia development [21]. For specific pathophysiology of dementia, the direct damage to brain tissue via ischemic stroke or intracranial hemorrhage is the mechanism of VD [22], and evensmall vessel disease can cause following VD episodes [23]. The AD, featured with the accumulation of both the protein beta-amyloid and tau tangles, leads to synapse decline and neuron death progressively [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is an elevation of caspase 3 RNA, and of matrix-metalloprotease 2 (MMP-2) expression [136,137], with a marked astrocytosis at the first part of the process, and then with their death (the following part has not been described in the post-RT brain, probably due to the long-lasting observation period, typical of SVD and not of post-RT) [138][139][140][141][142]. In SVD, the astrocytic death includes a severe alteration of the precarious neurovascular coupling system, leading to its destruction [143].…”
Section: Radiotherapy Damage and Small Vessel Disease: Common Pointsmentioning
confidence: 99%
“…The effects of the inflammation in the SVD act indirectly on the endothelium [143,144]. It is widely demonstrated that, due to an altered response to endothelium-derived nitric oxide-vasodilators [145,146], prostacyclin [147] and endothelium-derived hyperpolarizing factors (EDHF) [148], there is an accelerated mitochondrial senescence of the endothelium walls [144].…”
Section: Radiotherapy Damage and Small Vessel Disease: Common Pointsmentioning
confidence: 99%
See 1 more Smart Citation